1
$\begingroup$

I'm trying to solve a complicated summation problem where there are two multiplication problems that both have $i$. I'm entirely lost. I would be thankful for any help.

How is it possible to possible to find the sum of this expression (with a proof)?

$$\sum_{i=1}^{n} i(2^i)$$

$\endgroup$
1
$\begingroup$

You can evaluate this sum by rearranging the terms:

\begin{align*} \sum_{i=1}^n i(2^i) &= 2^1 + 2\cdot2^2 + 3\cdot 2^3 + \cdots + n\cdot 2^n\\ &= \sum_{i=1}^n 2^i + \sum_{i=2}^n 2^i + \sum_{i=3}^n 2^i +\cdots + 2^n\\ &= (2^{n+1} - 2^1) + (2^{n+1}-2^2) + (2^{n+1} - 2^3) + \cdots + (2^{n+1} - 2^n)\\ &= n2^{n+1} - \sum_{i=1}^n 2^i = n2^{n+1} - (2^{n+1} - 2) = (n-1)2^{n+1} + 2 \end{align*}

If you participate in a lot of math competitions, this trick is a handy one to know.

$\endgroup$
  • $\begingroup$ that is a very handy trick I would never had gotten. Thank you very much. $\endgroup$ – ik629 Feb 23 at 23:17
1
$\begingroup$

Here is another approach, which yields a more general result. Start with the formula for the sum of a geometric series. $$\sum_{i=0}^n x^i = \frac{1-x^{n+1}}{1-x}$$ Differentiate with respect to $x$. $$\sum_{i=0}^n i x^{i-1} = \frac{n x^{n+1}-(n+1)x^n+1}{(1-x)^2}$$ Multiply by $x$. $$\sum_{i=1}^n i x^i =\sum_{i=0}^n i x^i = x \left( \frac{n x^{n+1}-(n+1)x^n+1}{(1-x)^2} \right)$$ Now take the special case $x=2$. $$\sum_{i=1}^n i 2^i = 2\;[n 2^{n+1}-(n+1)2^n+1]$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.